A polyoxometalate-based polymer electrolyte with an improved electrode interface and ion conductivity for high-safety all-solid-state batteries. Issue 26 (18th June 2019) - Yuan, Xiangfei; Sun, Cui; Duan, Jia-Ning; Fan, Jingmin; Yuan, Ruming; Chen, Jiajia; Chang, Jeng-Kuei; Zheng, Mingsen; Dong, Quanfeng
Abstract : By combining inorganic LVC with organic PEO matrix, a polyoxometalate-based polymer electrolyte (PPE) was constructed for solid state batteries. Abstract : Solid electrolytes have been considered as some of the most promising candidates for next generation lithium-based batteries because they eliminate the potential safety hazards of liquid organic electrolytes and further increase the energy density of batteries. However, inherent defects such as low conductivity and poor interface compatibility with electrodes critically hinder their extensive application. Polyoxometalate Li7 [V15 O36 (CO3 )] (LVC) can dissociate Li + in electrolyte and possesses a high diffusion coefficient, which constitute a pathway for Li + transmission. Herein, a polyoxometalate-based polymer electrolyte (PPE) with an improved electrode interface and ion conductivity for high-safety all-solid-state batteries has been designed and synthesized to further enhance their electrochemistry behaviour. Compared with the routine PEO18 LiTFSI electrolyte, the ionic conductivity was enhanced. Meanwhile, LVC can improve the interface compatibility between the electrode and electrolyte significantly, which promotes reaction kinetics and suppresses lithium dendrites against Li metal. When employed in LiFePO4 |Li batteries, the specific discharge capacity after 180 cycles reached 148 mA h g −1 with a high coulombic efficiency of around 99.9% at 0.5C. According to the result of ARC, LiFePO4 |C batteries with PPEs are endowed with superior safety as the onset temperature of the self-heating process reaches up to 181.4 °C and the thermal runaway process does not occur within the range of 360 °C, indicating the potential of the PPE for high-safety all-solid-state batteries.